MyVetPBLTM : a problem-based learning (PBL) tool for veterinary education in Universiti Putra Malaysia (UPM) - Shaik Mohamed Mossadeq, Wan Mastura; Selvarajah, Gayathri Thevi; Arshad, Siti Suri; Ahmad, Idawaty; Hamdan, Hazlina (UTM Academic Leadership (UTMLead), Universiti Teknologi Malaysia, 2016)
Problem-Based Learning (PBL) is an approach that incorporates soft skill with content learning and independent learning style as opposed to the teacher-centered learning practiced in universities. However, its implementation is time consuming and burdensome, involving countless paper-based assessments to be graded. Therefore MyVetPBL™, an e-learning tool for veterinary students as a paperless initiative to combat these problems was developed using a Software Development Life Cycle (SDLC) and implemented using Java, PHP language and MySQL database. The integration of e-learning tool with the PBL approach will hopefully enhance teaching and learning in undergraduate veterinary education in Universiti Putra Malaysia.